2014
DOI: 10.1016/j.vetmic.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Lung pathogenicity of European genotype 3 strain porcine reproductive and respiratory syndrome virus (PRRSV) differs from that of subtype 1 strains

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is difficult to control due to a high mutation rate of the PRRS virus (PRRSV) and the emergence of virulent strains. The objective of this study was to analyse early and late pathological responses in the respiratory tract after infection with the European PRRSV subtype 3 strain Lena in comparison to two European PRRSV subtype 1 strains: Belgium A and Lelystad-Ter Huurne (LV). For each virus strain, groups of twelve pigs were inoculated, and four pigs per gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 33 publications
3
36
0
Order By: Relevance
“…In the present study, we compared clinical signs, virological parameters, seroconversion, APP response and histopathological lesions in pigs infected with either the Danish strain 18794 from subtype 1, the Russian strain ILI6 from subtype 2, and the Belarusian strain BOR59 from subtype 2, all belonging to PRRSV-1. The results indicated that BOR59 strain can be considered a highly virulent strain, similarly to subtype 3 strains Lena and SU1-bel (Karniychuk et al, 2010;Morgan et al, 2013;Weesendorp et al, 2013aWeesendorp et al, , 2014.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the present study, we compared clinical signs, virological parameters, seroconversion, APP response and histopathological lesions in pigs infected with either the Danish strain 18794 from subtype 1, the Russian strain ILI6 from subtype 2, and the Belarusian strain BOR59 from subtype 2, all belonging to PRRSV-1. The results indicated that BOR59 strain can be considered a highly virulent strain, similarly to subtype 3 strains Lena and SU1-bel (Karniychuk et al, 2010;Morgan et al, 2013;Weesendorp et al, 2013aWeesendorp et al, , 2014.…”
Section: Discussionmentioning
confidence: 91%
“…It has been shown that, in terms of virulence, antigenic characteristics and immunological responses following experimental infection, the Belarusian Lena subtype 3 strain differed from subtype 1 strains from Western Europe being generally more pathogenic for pigs (Karniychuk et al, 2010;Weesendorp et al, 2013aWeesendorp et al, , 2014. Later, another subtype 3 Belarusian strain SU1-bel, which was characterized in vitro and in in vivo challenge experiments also proved to be significantly more virulent than Western European strains (Morgan et al, 2014(Morgan et al, , 2013Salguero et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…SDOW17 is one of the most commonly used anti-N mAb which is considered to recognize N of nearly all European and North American PRRSV isolates except the PrimePac PRRS vaccine virus [31, 34, 40]. Accordingly, the SDOW17 mAb has been widely applied in immunohistochemistry [41, 42], immunofluorescence [4345], virus titration [46], and flow cytometry [43, 47]. However, SDOW17 failed to detect the virus that caused the short PRRSV outbreak in Switzerland in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Although first reported over 25 years ago, PRRS remains a severe disease and causes huge economic losses in pig production worldwide (Meulenberg et al, 1993;Nathues et al, 2014;Tian et al, 2007;Tornimbene et al, 2015;Zhou & Yang, 2010). The most important pathological characteristics of PRRS are lung inflammation, loss of epithelial barrier function, immune cell migration, and increased vascular permeability (Han et al, 2014;Weesendorp et al, 2014). PRRSV mainly replicates in lungs, tonsils and lymphoid organs, and induces a persistent viral infection.…”
mentioning
confidence: 99%